2011
DOI: 10.1007/s10494-011-9326-3
|View full text |Cite
|
Sign up to set email alerts
|

Friction Drag Variation via Spanwise Transversal Surface Waves

Abstract: The introduction of spanwise velocity is a promising technique to effect the near-wall turbulent flow field to influence friction drag. However, the essential physical mechanism which significantly reduces friction drag has not been understood, yet. It is the objective of this numerical study to improve the fundamental knowledge on the drag reduction mechanism. The investigation is based on spanwise traveling transversal surface waves which are applied to modify the near-wall flow field and to influence fricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…On the other hand, with increasing amplitude a higher drag reduction was obtained. Similar to the results of [10] they also found a strong correlation between the drag reduction and the reduction of the wall-normal vorticity component.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…On the other hand, with increasing amplitude a higher drag reduction was obtained. Similar to the results of [10] they also found a strong correlation between the drag reduction and the reduction of the wall-normal vorticity component.…”
Section: Introductionsupporting
confidence: 85%
“…In a more recent analysis extending the previous investigation Tamano and Itoh [21] achieved 13% drag reduction. Klumpp et al [8,10] performed large-eddy simulations (LES) of turbulent boundary layers at Re θ = 887 over transversal traveling surface waves. Through the analysis of two distinct parameter configurations λ + = 174 and λ + = 870 it was possible to reveal a different impact on the skin-friction distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, Klumpp et al [51,52] performed a numerical simulation of a spatially evolving turbulent boundary layer over spanwise traveling transversal sinusoidal surface waves for a compressible flow at a low Mach number. They showed that a drag reduction ratio up to 9% could be obtained, and that two key features for drag reduction were the damping of the wall-normal vorticity fluctuations above the entire surface and the decrease of turbulence production.…”
Section: Introductionmentioning
confidence: 99%
“…This caused the suppression of quasi-streamwise vortices within the boundary layer. A further numerical investigation was conducted by Klumpp et al (2011). In their large-eddy simulation (LES), the outof-plane motion of a spanwise surface wave was implemented in a turbulent channel flow and achieved a skinfriction drag reduction of 9 %.…”
Section: Transverse Wall Motionsmentioning
confidence: 99%